Condutividade elétrica em diferentes partes de sementes de soja - Cunha, Cristina dos Santos Madruga (2010)
Among the rapid tests, the electrical conductivity has been used for the evaluation of seed vigor, since the process of deterioration of the initial events is the loss of membrane integrity. The objective was to evaluate the efficiency of electrical conductivity mass and individual, driven to different parts of soybean seeds (whole seed, cotyledons and embryonic axes) and verify the possibility of obtaining results in less than 24 hours. The electrical conductivity and mass were conducted in individual laboratories Didactic Analysis of Seed Plant Science Department, Faculty of Agronomy "Eliseu Maciel (UFPel) and Universidade Federal de Santa Maria (UFSM), respectively. We used seeds of two cultivars, each represented by six lots. The physiological seed quality was evaluated by standard germination, first count germination, seedling vigor classification, accelerated aging, a field emergence and electrical conductivity. To conduct the electrical conductivity mass of the different structures of the seed, there were four replicates of each batch, with 10 whole seeds, embryonic axes 10 and 10 pairs of cotyledons submerged in 25mL of distilled and deionized water for the following periods: 1, 2 , 3, 4, 5, 6, 7, 8 and 24 hours. As the system mass, electrical conductivity of the different structures of the individual seed, there were four replicates of each batch. Whole seeds were submerged in 5mL of distilled and deionized water for 24 hours as well as the embryonic axes and cotyledons pairs of the following periods: 1, 2, 3, 4, 5 and 6 hours. The electrical conductivity test conducted with embryonic axes mass is promising for evaluating the effect of soya, showing efficiency in the stratification of lots with respect to physiological potential; The effect of soybean seeds can be determined by electrical conductivity mass, using 10 embryonic axes immersed in 25mL of deionized water and imbibed for one hour at 25 ° C.